(untitled) (Research, Society and Development, 2021)
Introduction: Mobile health (mHealth) apps have been involved in contemporary clinical practice in potential drug-drug interactions (pDDIs) research. However, available pDDIs information may differ between apps, which could impact the success of patient’s drug therapy. This study analyzed the performance of the mHealth apps in a context of pharmacotherapy prescribed to HIV/AIDS hospitalized patients. Methods: Cross-sectional study was conducted in a referral hospital for infectious diseases, central Brazil. Drug prescriptions were selected randomly by census. A pDDIs prevalence, severity classification as well the agreement of information and performance of different mHealth checkers were analyzed. Free access mHealth apps were selected: Drugs®, EpocratesRx®, and Micromedex® (considered as reference app). Analysis of sensitivity, specificity, positive or negative predictive values (PPV or NPV) was conducted. Results: The majority of 33 HIV/AIDS hospitalized patients was males, young adults, with opportunistic infections despite of a recent HIV diagnosis. 373 drugs were prescribed with 461 pDDIs identified by mHealth checkers. The pDDIs prevalence was 13.9% (12.4-15.6), 22.2% (20.1-24.5) and 24.8% (22.9-26.8) in Micromedex®, EpocratesRx® and Drugs®, respectively. Micromedex® classified most of pDDIs (71.2%) as major, while Drugs® (67.6%) and EpocratesRx® (84.8%) classified most of them as minor. In comparison with Micromedex®, Drugs® or EpocratesRx® showed none (K<0.00) or little (K=0.11) agreement in identification of pDDIs, respectively. Performance analyzes showed that Drugs® presented greater sensitivity (75.4%), however, the results of specificity, PPV, NPV, and accuracy were similar by both apps when compared to the reference. Conclusion: The mHealth drug interaction checkers presented important divergences in the results of identification, classification of severity and prevalence rate of pDDIs.